Beyond Development: Postdevelopment and Transitions towards the Pluriverse - Escobar, Arturo (Revista de Antropología Social, 2012)
The present text constitutes the Preface to the second edition Encountering Development (1995). After reviewing both the most important transformations in the world over the past fiffteen years, and the debates in critical development studies during the same period, the author concludes that the time has come to renew the debates on postdevelopment and alternatives to development, as many social movements are actually doing. Given the deepening ecological and social crises, there emerge in undeniable ways discourses about transitions to an other type or society or civilizational model. This transition could move us beyond the modern idea of one Universe –One World under the hegemony of certain conceptions of the individual, rationality, economy, science, and the market—towards a genuine pluriverse of scio-natural worlds. These transitions announce that globalization is not only the last stage of capitalist modernity, but also the beginning of something new.